Toward Automatic Rhodopsin Modeling as a Tool for High-Throughput Computational Photobiology - Melaccio, Federico; Del Carmen Marín, María; Valentini, Alessio; Montisci, Fabio; Rinaldi, Silvia; Cherubini, Marco; Yang, Xuchun; Kato, Yoshitaka; Stenrup, Michael; Orozco-Gonzalez, Yoelvis; Ferré, Nicolas; Luk, Hoi Ling; et al. (Journal of chemical theory and computation, 2016)
We report on a prototype protocol for the automatic and fast construction of congruous sets of QM/MM models of rhodopsin-like photoreceptors and of their mutants. In the present implementation the information required for the construction of each model is essentially a crystallographic structure or a comparative model complemented with information on the protonation state of ionizable side chains and distributions of external counterions. Starting with such information, a model formed by a fixed environment system, a flexible cavity system, and a chromophore system is automatically generated. The results of the predicted vertical excitation energy for 27 different rhodopsins including vertebrate, invertebrate, and microbial pigments indicate that such basic models could be employed for predicting trends in spectral changes and/or correlate the spectral changes with structural variations in large sets of proteins.